Decreased Susceptibility to Ciprofloxacin among Shigella Isolates in the United States, 2006 to 2009 - Folster, Jason P. (American Society for Microbiology (ASM), 2011)
We characterized 20 Shigella isolates with decreased susceptibility to fluoroquinolones. Most patients (80%) from whom a travel history was obtained reported travel to South or Southeast Asia. Mutations within the quinolone resistance determining regions of gyrA and parC and plasmid-mediated resistance determinants (qnrB, qnrS, and aac(6′)-Ib-cr) were identified. The rise in antimicrobial resistance among Shigella isolates may necessitate the increased use of extended-spectrum cephalosporins or macrolides in some patients.